Integrasi Health Belief Model dan Theory of Planned Behavior untuk Memprediksi Niat Konsumsi Produk Rendah Gula pada Mahasiswa - Mohammad Haidar Ali; Sanaji Sanaji; Anik Lestari Andjarwati (Jurnal Ilmu Manajemen, 2025)
This study examines the effects of perceived benefits, perceived barriers, and health motivation on attitudes, and the subsequent influence of attitudes on the intention to consume low-sugar products among students at Universitas Hasyim Asy’ari, Jombang, Indonesia. Integrating the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB), this explanatory quantitative research applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to data collected from 100 purposively selected students. The analysis reveals that perceived benefits and health motivation significantly and positively affect attitudes, while perceived barriers show no significant influence. Attitudes emerge as the main predictor of the intention to adopt low-sugar consumption behaviors. Theoretically, these findings strengthen the understanding that intrinsic motivation and perceived benefits can overcome external barriers in shaping health intentions, especially within a collectivist cultural context. Practically, the study highlights the importance of participatory, value-driven social marketing campaigns that resonate with students’ emotional, moral, and social values. Effective interventions should not rely solely on rational health information but also engage young audiences through relatable narratives, role models, and community-based approaches. Overall, this research offers both theoretical insights and practical recommendations for designing culturally sensitive strategies to promote sustainable healthy consumption behaviors among youth in developing countries.